2014
DOI: 10.4161/15384047.2014.955740
|View full text |Cite
|
Sign up to set email alerts
|

M2muscarinic receptors inhibit cell proliferation and migration in urothelial bladder cancer cells

Abstract: The role of muscarinic receptors in several diseases including cancer has recently emerged. To evaluate the hypothesis that muscarinic acetylcholine receptors may play a role in bladder cancer as well as in other tumor types, we investigated their expression in bladder tumor specimens. All examined samples expressed the M1, M2 and M3 receptor subtypes. We also found that the level of M2 transcripts, but not those of M1 or M3, significantly increased with the tumor histologic grade. In view of these results, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 44 publications
8
24
0
Order By: Relevance
“…First, we evaluated the cell toxicity exerted by EVOOE on two different BCa cell lines, T24 and 5637, which are characterized by two different grades and are widely used as in vitro models (3133) as they cover the more frequent subtypes of BCa. 5637 cells well represent the E2F3/RB1 pathway due to amplification of 6p22.3, concomitant with loss of one copy of RB1 and mutation of the other copy.…”
Section: Discussionmentioning
confidence: 99%
“…First, we evaluated the cell toxicity exerted by EVOOE on two different BCa cell lines, T24 and 5637, which are characterized by two different grades and are widely used as in vitro models (3133) as they cover the more frequent subtypes of BCa. 5637 cells well represent the E2F3/RB1 pathway due to amplification of 6p22.3, concomitant with loss of one copy of RB1 and mutation of the other copy.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of muscarinic receptors was also investigated in these Previous studies have already demonstrated the ability of arecaidine 305 to bind to M2 receptor, using pharmacological binding experiments and 306 M2 siRNA transfection [11][12][13][14][15]. By the same methodological approaches 307 we have now demonstrated that arecaidine is able to specifically bind 308 M2 receptors also in GSCs (Figs.…”
mentioning
confidence: 89%
“…Moreover, the contribution of muscarinic receptors in tumor 247 progression has been demonstrated[20] and the use of antagonists for 248 different muscarinic receptor subtypes is taking much attention for 249 cancer therapy[21]. Recently we have demonstrated the ability of 250 M2 receptor to influence tumor cell growth and survival both in GBM 251[10,11] and in urothelial bladder cancer cells[15]. ].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The long-term activation of these receptors with the agonist carbachol stimulates cytotoxicity either in human or in murine breast tumor cells [13,14]. In the last years, several reports demonstrated that the activation of M 2 receptor subtype by a selective agonist was able to arrest cell proliferation in different tumor cell lines [15-17]. Moreover, M 2 receptor activation reduced cell survival, inducing oxidative stress and severe apoptosis in malignant cells derived from human glioblastoma [17].…”
Section: Introductionmentioning
confidence: 99%